Thermo‐Adaptive Block Copolymer Structural Color Electronics - Park, Tae Hyun; Eoh, Hongkyu; Jung, Youngdoo; Lee, Geon‐Woo; Lee, Chang Eun; Kang, Han Sol; Lee, Junseok; Kim, Kwang‐Bum; Ryu, Du Yeol; Yu, Seunggun; Park, Cheolmin (Advanced functional materials, 2021)
Flexible electronics that enable the visualization of thermal energy have significant potential for various applications, such as thermal diagnosis, sensing and imaging, and displays. Thermo‐adaptive flexible electronic devices based on thin 1D block copolymer (BCP) photonic crystal (PC) films with self‐assembled periodic nanostructures are presented. By employing a thermo‐responsive polymer/non‐volatile hygroscopic ionic liquid (IL) blend on a BCP film, full visible structural colors (SCs) are developed because of the temperature‐dependent expansion and contraction of one BCP domain via IL injection and release, respectively, as a function of temperature. Reversible SC control of the bi‐layered BCP/IL polymer blend film from room temperature to 80 °C facilitates the development of various thermo‐adaptive SC flexible electronic devices including pixel arrays of reflective‐mode displays and capacitive sensing display. A flexible diagnostic thermal patch is demonstrated with the bi‐layered BCP/IL polymer blend enabling the visualization of local heat sources from the human body to microelectronic circuits. Thermo‐adaptive flexible electronic devices are demonstrated, based on thin 1D block copolymer photonic crystal films with self‐assembled periodic nanostructures. The reversible structural color of the thermo‐responsive polymer/non‐volatile hygroscopic ionic liquid blend on the block copolymer film facilitates the development of various thermo‐adaptive devices including pixel arrays of reflective‐mode displays and capacitive sensing display as well as diagnostic thermal patches.